Financial constraints and Islamic finance: Lesson learned from external financing perspective - Achmad Tohirin; Mohd Adib Ismail (Economic Journal of Emerging Markets, 2016)
This study examines the presence of financial constraints and explores the role of profit-loss sharing (PLS) in mitigating the problem of the financial constraints stemmed from the capital market imperfections. Using Malaysian listed companies’ data, this study finds that the financial constraints are present in the capital market. This finding implies the imperfect capital market. In Islamic PLS framework, there are two options of financing contracts that may be enforced in the capital market as financing mechanisms, i.e. al-musharakah and al-mudharabah. These schemes promote sharing of information and mutual trust between financiers and ‘borrowers’. In these contracts, there are strict terms and conditions to be adhered to by both parties so that the contracts pursue to be valid. Besides, PLS mechanism may reduce the cost of capital since the profit and loss are shared rather than be burdened only on one shoulder. In this regard, the imperfect market problems namely asymmetric information, agency problem and transaction cost can be reduced if not be overcome.